Meningkatkan Keamanan Energi Melalui Perincian Indikator Energi Terbarukan dan Efisiensi Guna Membangun Ketahanan Nasional Dari Daerah - Erkata Yandri; Ratna Ariati; Riki Firmandha Ibrahim (Jurnal Ketahanan Nasional, 2018)
ABSTRACT The purpose of this paper was to discussed how to developed the concept of Indonesia's energy security model with of Renewable Energy (RE) and Energy Efficiency (EE) programs. To did this, there were four important concepts must be completed: reconceptualized the Indonesia's energy security model; explained the energy security (ES) relationship with the details of the indicator; explained the potential of ET and EE in each sector; explained the role of local government in exploiting the potential of ET and EE.As an archipelago country  divided into several regions, in order to get accurate prediction, our result showed  that development Indonesian energy security models needed to be developed properly with more detailed indicators of RE and EE. To pursued the goal of national energy policy, the potential of RE and EE in each province should be utilized immediately, the role of local government was very important. The concept of detailed RE and EE indicators would create a contribution for local governments in realizing national energy security.ABSTRAKTujuan dari penulisan ini adalah untuk membahas bagaimana mengembangkan konsep model keamanan energi Indonesia dengan program Energi Terbarukan (ET) dan Efisiensi Energi (EE).Untuk melakukan ini, ada empat konsep penting yang harus diselesaikan: mengkonsepkan kembali model keamanan energi Indonesia; menjelaskan hubungan kemananan energi (ES) dengan perincian indikator; menjelaskan potensi ET dan EE di masing-masing sektor; menjelaskan peran pemerintah daerah dalam memanfaatkan potensi ET dan EE.Sebagai negara kepulauan yang terbagi menjadi beberapa provinsi,  analisis menunjukkan bahwa model keamanan energi Indonesia perlu dikembangkan dengan indikator ET dan EE yang lebih rinci. Untuk mengejar tujuan kebijakan energi nasional, potensi ET dan EE di setiap provinsi harus segera dimanfaatkan, maka peran pemerintah daerah sangat penting. Konsep model indikator ET dan EE yang terperinci ini akan merupakan kontribusi bagi pemerintah daerah dalam mewujudkan keamanan energi nasional.